Infectious Agents and Inflammation: The Role of Microbiota in Autoimmune Arthritis - Picchianti-Diamanti, Andrea; Rosado, Maria M.; D’Amelio, Raffaele (Frontiers in Microbiology, 2018)
In high vertebrates the mucosal sites, lining at the border between internal and external environment, directly interact with bacteria, viruses, and fungi. Through co-evolution, hosts were able to develop mechanisms of tolerance or ignorance towards some infectious agents, because hosts established a sort of “gain of function” interactions with symbiotic bacteria. Indeed, some bacteria help hosts in different functions, among which the digestion of complex carbohydrates, and the absorption and supply of vitamins. There is no doubt that microbiota modulates innate and acquired immune responses starting at birth and variations in quality and quantity of bacterial species interfere with the equilibrium between inflammation and tolerance. In fact, correlations between gut bacteria composition and the severity of inflammation have been first described in inflammatory bowel diseases and later extended to other pathologies. Genetic background, environmental factors like stress, smoke, and diet can induce strong bacterial changes and consequent exposure of the intestinal epithelium to a variety of different metabolites, many of which with still unknown function. In addition, alterations in gut permeability may allow pathogens entry, thus infection and/or chronic inflammation. In this context, a local event occurring at mucosal site may be the triggering cause of an autoimmune reaction involving far apart sites or organs. Recently, several studies attributed a pathogenic role to altered oral microbiota in rheumatoid arthritis (RA) and to gut dysbiosis in spondyloarthritis (SpA). There is also growing evidence that different drugs, such as antibiotic and immunosuppressant, can influence and be influenced by microbiota diversity and composition in RA and SpA patients. Hence, in complex disorders such RA and SpA, not only the genetic background, gender, and immunologic context of the individual are relevant, but also the history of infections and the structure of microbial community at mucosal sites should be considered. Here the role of the microbiota and infections in the start and progression of chronic arthritis is discussed, as well as how these factors can influence patient’s response to synthetic and biologic immunosuppressive therapy.